Effects of local administration of tiludronic acid on experimental periodontitis in diabetic rats. Issue 1 (6th February 2018) - Nunes, Nara L.T.; Messora, Michel R.; Oliveira, Luiz Fernando; Lisboa, Mario; Garcia, Marina Costa Barcellos; Rêgo, R.O.; Novaes, Arthur Belém; de Souza, Sérgio Luís Scombatti; Ervolino, Edilson; Furlaneto, Flávia A.C.
Abstract: Background: Tiludronic acid (TIL) presents antiresorptive and anti‐inflammatory properties and has not been evaluated in the periodontitis–diabetes mellitus (DM) association to date, to the best knowledge of the authors. This study evaluates effects of local administration of TIL on experimental periodontitis (EP) in rats with streptozotocin‐induced DM. Methods: Thirty‐two animals ( Rattus norvegicus albinus, Wistar) were divided into groups DM/C (Control), DM/EP, DM/EP/TIL1, and DM/EP/TIL3. In EP groups, a ligature was placed around mandibular first molars. In groups DM/EP/TIL1 and DM/EP/TIL3, TIL solutions (1 and 3 mg/kg, respectively) were injected into the gingival tissue of mandibular molars every other day for 10 days, until euthanasia. Periodontal tissues were analyzed by microcomputed tomography (micro‐CT), histomorphometry, immunohistochemistry (tartrate‐resistant acid phosphatase [TRAP], receptor activator of nuclear factor‐κB ligand [RANKL], osteoprotegerin, cleaved caspase 3), and quantitative reverse transcription‐polymerase chain reaction (interleukin [IL]‐1β, vascular endothelial growth factor [VEGF]). Results: In micro‐CT analyses, groups DM/EP/TIL1 and DM/EP/TIL3 presented reduced alveolar bone resorption ( P  < 0.05). Group DM/EP/TIL3 presented decreased attachment loss ( P  < 0.05). The amount of TRAP‐positive multinucleated cells was decreased in TIL groups ( P  < 0.05). Group DM/EP/TIL3 presented a lower immunolabeling pattern for RANKL ( P  < 0.05). TIL treatment decreased genic expression of IL‐1β, and in group DM/EP/TIL3, expression of VEGF was increased ( P  < 0.05). Conclusion: Local administration of TIL promoted a protective effect against tissue destruction in EP in diabetic rats, and the dosage of 3 mg/kg of TIL promoted the best results regarding its antiresorptive and anti‐inflammatory effects.